(untitled) (Bangladesh Journal of Botany, 2021)
Effects of manganese (Mn) toxicity stress on the growth of soybean, the number of Mn spots on leaves and the absorption of iron and magnesium were studied by nutrient solution hydroponics. The results showed that the presence of Mn spots on leaves was the main symptom of Mn toxicity in soybean. When the concentration of exogenous Mn was 25 μmol/l, the leaf generated obvious Mn oxidation spots; when the concentration of exogenous Mn exceeded 50 μmol/l, the growth of soybean was inhibited, and the number of Mn spots increased significantly. With the increase in exogenous Mn concentration, the Mn concentration in the roots, young leaves and old leaves of soybean increased significantly. When the concentration of exogenous Mn reached 200 μmol/l, the number of Mn spots on primary leaves, old leaves and young leaves increased significantly. Although the iron concentration in the roots remained the same, the iron content in the old and young leaves decreased significantly. On the other hand, although Mn toxicity significantly reduced the concentration of magnesium in soybean roots, it increased the concentration of magnesium in old and young leaves. Bangladesh J. Bot. 50(3): 803-811, 2021 (September) Special